Fase topológica fracionária em qudits fotônicos codificados espacialmente - Artur Araujo Matoso (2014)
In this work we propose two experimental setups to observe fractional topological phases in qudits. The degree of freedom in which the qudits are encoded is the transverse position of photon pairs generated by spontaneous parametric down-conversion after being transmitted through multiple slits. The photons generated in this phenomenonare quantum correlated in energy and momenta. Initially we discuss the basic theory about topological phases, the context in which they are fractional, and its relation with entanglement. Then, we see how local unitary operations can be applied in this degree of freedom with the aid of spatial light modulators that introduce a programmable phase prole on the wavefront of the photons. Thus, the desired fractional phases canbe observed through polarization-controlled two-photon interference. The roles played by entanglement and Hilbert space dimension are revealed by the behavior of the interference fringes as the unitary operations are continuously changed. These ideas are supported by analytical and numerical calculations of the expected interference fringes. We also show how the so called Hong-Ou-Mandel eect is present in the proposed interferometer, which requires simultaneity on the recombination of the photons generated to allow for the interference